Gambling Marketing Strategies and the Internet: What Do We Know? A Systematic Review - Guillou-Landreat, Morgane; Gallopel-Morvan, Karine; Lever, Delphine; Le Goff, Delphine; Le Reste, Jean-Yves (Frontiers in Psychiatry, 2021)
Background The gambling industry has developed many types of gambling on Internet in recent years. Gambling is a social activity for a majority of the world population, but problem gambling (PG) can emerge. The trajectories of gamblers from initiation to PG development are influenced by many variables, including individual and environmental variables and also variables linked to the gambling characteristics. Marketing has been reported to influence gamblers' perceptions and behaviours, but this is not as clear for digital marketing. Digital gambling marketing is broad, ranging from the marketing of gambling websites to communication and advertising on the social media and networks. The objective of this article was to fill this gap by conducting a systematic literature review in order to answer the following questions: 1/ What are the strategies of digital gambling marketing? 2/ What is the effect of this exposure on gambling representations, intentions and practices? Method A systematic review was conducted following the PRISMA guidelines on Pubmed database (Medline) from February 2020 to March 2020. Existing papers published between January 2000 and February 2020 were identified by searching with this algorithm : ((("internet"[MeSH Major Topic] OR (communications[All Fields] AND media[All Fields])) OR ("social media"[MeSH Terms] OR ("social"[All Fields] AND "media"[All Fields]) OR "social media"[All Fields])) AND "gambling"[MeSH Major Topic]) AND ("marketing"[MeSH Terms] OR "marketing"[All Fields]), in title , keywords or abstract. Results Sixty-four candidate studies were selected ,20 studies were selected for the systematic review. Sport appeared as a specific target of online gambling marketing. A growing range of platforms for online sport betting and the development of strategies on the social media were identified. Regarding content, a systematic association between sport and gambling was highlighted. Vulnerable populations, such as young people, appeared to be at high risk of exposure to gambling marketing. Conclusion Little data is available on the strategies of digital gambling marketing nor on exposure to it. Sport could be the first target for future research to understand how the industry is targeting specific populations, and what influence these strategies could have on PG development.